2018
DOI: 10.3389/fmicb.2018.01401
|View full text |Cite|
|
Sign up to set email alerts
|

Stoichiometric Shifts in Soil C:N:P Promote Bacterial Taxa Dominance, Maintain Biodiversity, and Deconstruct Community Assemblages

Abstract: Imbalances in C:N:P supply ratios may cause bacterial resource limitations and constrain biogeochemical processes, but the importance of shifts in soil stoichiometry are complicated by the nearly limitless interactions between an immensely rich species pool and a multiple chemical resource forms. To more clearly identify the impact of soil C:N:P on bacteria, we evaluated the cumulative effects of single and coupled long-term nutrient additions (i.e., C as mannitol, N as equal concentrations NH4+ and NO3−, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 109 publications
4
29
1
Order By: Relevance
“…McKnight et al (2007) also demonstrated a rapid increase in cyanobacterial mat biomass and biological activity after introduction of water to a relic stream, showing that biological communities maintain the potential to respond quickly to renewed flow (McKnight et al, 2007). While these experiments differed substantially from the wetting experiment described here, results of these and other studies (e.g., Schwartz et al, 2014; Aanderud et al, 2018) demonstrate that endemic communities in the MDV can respond within timeframes considerably shorter than previously hypothesized, thereby challenging long-held perceptions regarding the MDV of extremely slow response rates (Burkins et al, 2001; Elberling et al, 2006; Barrett et al, 2007).…”
Section: Discussioncontrasting
confidence: 74%
“…McKnight et al (2007) also demonstrated a rapid increase in cyanobacterial mat biomass and biological activity after introduction of water to a relic stream, showing that biological communities maintain the potential to respond quickly to renewed flow (McKnight et al, 2007). While these experiments differed substantially from the wetting experiment described here, results of these and other studies (e.g., Schwartz et al, 2014; Aanderud et al, 2018) demonstrate that endemic communities in the MDV can respond within timeframes considerably shorter than previously hypothesized, thereby challenging long-held perceptions regarding the MDV of extremely slow response rates (Burkins et al, 2001; Elberling et al, 2006; Barrett et al, 2007).…”
Section: Discussioncontrasting
confidence: 74%
“…Changes in media (water or soil) N:P ratios affect the structure of terrestrial (Fanin et al, ; Scharler et al, ; Zechmeister‐Bolstenstren et al, ) and aquatic (Sitters, Atkinson, Guelzow, Kelly, & Sullivan, ) food webs, but associated impacts on community diversity are unclear. For example, some studies have reported increases in N:P ratios due to N deposition or land‐use change associated with reduced diversity of microbes (Zhang, Chen, & Ruan, ), plants (DeMalach, ; Güsewell, Bailey, Roem, & Bedford, ), and animals (Vogels, Verbek, Lamers, & Siepel, ; Wei et al, ), but other studies have found increases in microbial (Aanderud et al, ; Ren et al, ; ) and plant (Laliberté et al, ; Pekin, Boer, Wittkuhn, Macfarlane, & Grieson, ; Wassen et al, ; Yang et al, ) diversity. The diversity of plant species has been associated with an optimum plant N:P mass ratio near 20 (Sasaki et al, ), but the tendency for biodiversity to depend on concentrations of N and P in soil hinders the establishment of a generalized hypothesis for the relationship between N:P ratios and diversity for all components of terrestrial communities (DeMalach, ).…”
Section: Impacts Of Shifts In the N:p Ratios Of Human Inputs On Organmentioning
confidence: 99%
“…The ratio of C:N in natural environments such as soil affects bacterial diversity and growth and is often tuned in order to favor desired bacterial metabolisms in industrial settings (42, 43). It is therefore notable that even when grown in pyruvate defined medium with no ammonium (117 mM carbon, 5.5 mM nitrogen, C:N of the medium = 21.4, equal to glycerol defined medium), M. smegmatis had a relatively low cellular C:N ratio of 5.23 (stdev 0.38, p = 0.01 compared to glycerol grown cells) and grew as mostly planktonic cells (Fig.…”
Section: Resultsmentioning
confidence: 99%